Analisis Tatar Perilaku sebagai Langkah Awal untuk Membangun Desain Interior Sarana Pendidikan Anak Autis - Kharista Astrini Sakya; Imam Santosa; Andar Bagus Sriwarno; Indun Lestari (Unika Soegijapranata Semarang, 2020)
Empowering interior design to lead to better development can be done from small things such as paying attention to the means of education for autistic children. Interior designers can play a role in building educational facilities in accordance with the behavior of children with autism. Autistic behavior can be caused by not being able to process information properly from the stimuli of the physical environment (space) around it. The purpose of this study is to analyze the behavior of children with autism as a first step if they want to build an interior design for children with autism education in accordance with the behavior, so it is expected that if they know the behavior in the room, then the interior designer can design the educational facilities according to their needs and will maximum. The limitation of this study is only to analyze the behavior of autistic children in the therapy room according to the researcher's perspective as an interior designer. The method used is observation of children's behavior in the room during the therapy process, using video recorders. Analysis was carried out by anova statistical test. The results showed that there were differences in the number of children's behavior in the room when with the therapist and when alone. Before the therapy process takes place, the child will carry out the adaptation phase, showing curiosity whether the space / object makes the child comfortable / uncomfortable. In addition, children have the same behavior that is easily distracted with interior elements.